The Effect Analysis of Coating Thickness Variation and Mixed Composition of Zinc - Graphite on Epoxy Coating with Steel Plate ASTM A36 - Herman Pratikno; Andry Febrianto; Wimala Lalitya Dhanistha (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2020)
Steel has an important role in the world of marine manufacturing industry. Steel for offshore buildings needs to be reviewed in terms of controlling metal corrosion. The coating method can be used in mobilization areas and splash zones of offshore buildings that have high corrosion rates due to sustained friction loads in the marine environment. This study used steel plate ASTM A36, which is a low carbon steel, and analyze its adhesion strength, abrasion resistance, and corrosion rate prediction by varying the coating thickness of 100μm, 200μm, and 300μm, with a mixture of Zinc-Graphite on epoxy coatings of 2%, 6%, and 10 %. In the Pull-Off test the highest value of adhesion strength was obtained at a mixture of 2% and coating thickness of 100μm with a value of 8.73 Mpa. In the highest abrasion test values was obtained with a variation of 10% mixture and coating thickness of 300μm with a value of 0.91 Wear Cyces per Micrometer. Whereas in the three-cell electrode test the highest value was at a 100% mixture variation and coating thickness of 300μm with a value of 0,00010 mmpy.